Estudis actuals de Filologia Catalana. - JOSÉ MOMPEÁN-MEJÍAS, MARÍA (Scripta)
The article presents a review of the book "Estudis actuals de Filologia Catalana," edited by M. Isabel Guardiola Savall and Caterina Martínez-Martínez, which compiles research on the main lines of work in contemporary Catalan studies. This volume, which pays tribute to Professor Antoni Ferrando, includes eighteen studies organized into three thematic axes: linguistics, literature, and the teaching of language and literature. The chapters address topics such as the evolution of the definite article in Old Catalan, medieval literature, and innovative teaching proposals, thus reflecting the advances in the study of the Catalan language and literature in the Valencian Community.